18
$\begingroup$

Evaluation of $$\int\frac{(1+x^2)(2+x^2)}{(x\cos x+\sin x)^4}dx$$

$\bf{My\; Try::}$ We can write $$x\cos x+\sin x= \sqrt{1+x^2}\left\{\frac{x}{\sqrt{1+x^2}}\cdot \cos x+\frac{1}{\sqrt{1+x^2}}\cdot \sin x\right\}$$

So we get $$(x\cos x+\sin x) = \sqrt{1+x^2}\cos(x-\alpha)\;,$$ Where $\displaystyle \alpha = \tan^{-1}\left(\frac{1}{x}\right)$

So Integral $$I = \int\frac{(1+x^2)(2+x^2)}{(1+x^2)^2\cdot \cos^4 (x-\alpha)}dx = \int\frac{(2+x^2)}{(1+x^2)}\cdot \sec^4 (x-\alpha)dx$$

Now how can i solve after that,Help me

Thanks

$\endgroup$
  • $\begingroup$ Is this from some kind of olympiad $\endgroup$ – Archis Welankar Mar 15 '16 at 13:28
  • $\begingroup$ Wolframalpha gives some very big answer $\endgroup$ – Archis Welankar Mar 15 '16 at 13:37
  • $\begingroup$ @archiswelankar link? $\endgroup$ – zz20s Mar 15 '16 at 14:45
  • $\begingroup$ Sorry at that time i was on mobile within 20 mins ill post the link $\endgroup$ – Archis Welankar Mar 15 '16 at 16:01
  • 2
    $\begingroup$ Thanks friends I have got it, using $x-\cot^{-}(x) =t,$ Then $\left(\frac{2+x^2}{1+x^2}\right)dx=dt$ $\endgroup$ – juantheron Mar 15 '16 at 16:50
3
$\begingroup$

Your integral becomes $$I=\int { \frac { \left( 2+{ x }^{ 2 } \right) }{ \left( 1+{ x }^{ 2 } \right) } { \left( \sec { \left( x-\cot ^{ -1 }{ x } \right) } \right) }^{ 4 } } dx$$

On substituting $$\left( x-\cot ^{ -1 }{ x } \right) =t$$

diffrentiating $$dt = \frac { \left( 2+{ x }^{ 2 } \right) }{ \left( 1+{ x }^{ 2 } \right) } dx$$

Integration becomes $$I=\int { { \sec { \left( t \right) } }^{ 4 } } dt$$

Using : $\quad \quad \sec ^{ 2 }{ \left( x \right) } -\tan ^{ 2 }{ \left( x \right) } =1$

$$I=\int { { \sec { \left( t \right) } }^{ 2 } } \left( { \tan { \left( t \right) } }^{ 2 }+1 \right) dt$$

Again substituting $$\tan{ \left (t\right)} = u$$ $$du = { { \sec { \left( t \right) } }^{ 2 } }dt$$

Intrgration becomes $$I = \int { \left( { u }^{ 2 }+1 \right) du } $$

$$I=\frac { { u }^{ 3 } }{ 3 } +u+c$$ Substituting value of u $$I = \frac { { \tan { \left( t \right) } }^{ 3 } }{ 3 } +\tan { \left( t \right) } +c$$

$$I=\frac { { \tan { \left( x-\cot ^{ -1 }{ x } \right) } }^{ 3 } }{ 3 } +\tan { \left( x-\cot ^{ -1 }{ x } \right) } +c$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.